Conscious Coastal Cities Sustainability, Blue Green Growth, and The Politics of Imagination - Mega, Voula P. (Springer International Publishing : Imprint: Springer, 2016)
In our age of dynamic urban geopolitics, cooperation between major city networks, enriched and strengthened by their various initiatives, have made it possible for interconnected coastal cities to move forward towards a more resilient sustainable future. This book is a step towards raising global awareness of the challenges and opportunities faced by coastal cities and the myriad issues and stakeholders that impact them. The authors of this book offer a panoramic, integrated, view of the most critical urban coastal sustainability issues that will continue to define the urban horizon of the future. Drawing on the most authoritative studies and probing deeply into further questions, the book embraces a rich program of issues that can assure growing strength of our urban geopolitics.  Among these issues are: smart, sustainable and inclusive blue green growth, active social integration, environmental conscience and resilience, food, energy and resource security, exploration and protection of the global ocean, ecosystem-based urban coastal planning and policy and progress in education and science, culture and the arts, coastal urban renaissance, and accountable multi-layered governance. From large global ports to small tourism and fishing resorts, sustainable development calls for coastal cities to improve their functions. Coastal cities need to adopt ecosystem-based approaches to manage the land-sea continuum, invest in blue green energy and mobility, attract responsible business investment, and honour the sea as a source of infinite innovation and culture. Intelligent and dynamic solutions to the problems of our many issues will unarguably result in better lives for generations to come. It is our hope that this book will be a major influence on scholars, teachers, scientists, engineers and other shareholders in this crucial move into the future.